Primera aproximación de carga animal óptima en cuyes al pastoreo durante la época lluviosa en la sierra peruana - Anaya L., Liz (2021)
The present study carried out a first approximation of the optimum stocking rate in guinea pigs grazing during the rainy season in the Peruvian highlands, using an associated perennial pasture composed of Lolium multiflorum, Lolium perenne, Dactylis glomerata, Trifolium pratense, Trifolium repens y Medicago sativa based on individual body weight gain and per area, feed intake, feed conversion, pasture yield, production costs and cost benefit ratio. In total, 132 15-day-old male G guinea pigs were used in a randomized complete block design with three 60-day fattening cycles as a block and four treatments corresponding to stocking rates of 400 (T1), 500 (T2), 600 (T3) and 700 (T4) guinea pigs/ha/year. It was used areas of 200 m2 of pasture where groups of 8, 10, 12 and 14 guinea pigs grazed in T1, T2, T3 and T4, respectively. The results showed that there was no effect of the stocking rate on individual body weight gain, feed intake, feed conversion and pasture performance yield (>0.05). The effects on the gain per unit area and cost benefit ratio (p<0.05) were a direct and expected consequence of the different number of animals between stockings. The range of stocking rates was insufficient to determine an optimal stocking rate, so it is tentatively suggested to use the stocking rate of 700 guinea pigs/ha/year, as it is the stocking rate that allows more animals per area with productive parameters similar to lower stocking rates and better economic parameters.